Effects of Nordic Walking and Pilates training programs on aminotransferase activity in overweight and obese elderly women - Hagner-Derengowska, Magdalena; Kałużny, Krystian; Budzyński, Jacek (Journal of Education, Health and Sport, 2015)
Hagner-Derengowska Magdalena, Kałużny Krystian, Budzyński Jacek. Effects of Nordic Walking and Pilates training programs on aminotransferase activity in overweight and obese elderly women. Journal of Education, Health and Sport. 2015;5(12):563-580. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44249 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A563-580 http://pbn.nauka.gov.pl/works/687148 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. Effects of Nordic Walking and Pilates training programs on aminotransferase activity in overweight and obese elderly women Magdalena Hagner-Derengowska1, Krystian Kałużny2, Jacek Budzyński3 1 Chair of Clinical Neuropsychology, Faculty of Health Sciences, Nicolaus Copernicus University in Toruń, Poland 2 Chair and Clinic of Rehabilitation, Faculty of Health Sciences, Nicolaus Copernicus University in Toruń, Poland 3 Chair of Vascular and Internal Diseases, Faculty of Health Sciences, Nicolaus Copernicus University in Toruń, Poland Corresponding author: Magdalena Hagner-Derengowska, PT, PhD Chair of Clinical Neuropsychology, Nicolaus Copernicus University in Toruń M. Skłodowskiej-Curie 9 Street, 85-094 Bydgoszcz, Poland E-mail address: m_hagner-derengowska@wp.pl ABSTRACT Background & Aims: Elevation of alanine (ALT) and aspartate aminotransferase (AST) activities may appear as liver injury due to fat storage and other enzyme sources, such as rhabdomyolysis. Elevated ALT is associated with all-cause and cardiovascular mortality in an elderly population. The aims of this study was to determine the effect of a 10-weeks training program on the serum activity of these enzymes in postmenopausal women with overweight and obesity. Methods: The study comprised 81 postmenopausal women with overweight and obesity: 34 (42%) of whom completed a 10-weeks Nordic Walking (NW) rehabilitation program, 27 (33%) of whom completed a Pilates rehabilitation program, and 20 (25%) of whom were the control group. Blood for testing for ALT, AST, and other parameters of metabolic syndrome was collected before the program commenced and after it finished. Results: Elevated (> 34 U/l) ALT and AST activities presented in 9 (11%) and 7 (9%) of the patients, respectively. A reduction in ALT and AST activities was observed in 43 (53%) of the subjects, and in 61%, 59% and 40%, and 47%, 63% and 50% of the individuals who completed the NW and Pilates programs and were in the control group, respectively. Conclusions: The outcome of the training programs on aminotransferase serum activities in postmenopausal women with overweight and obesity was individually different and not related to exercise type. Keywords: alanine aminotransferase, aspartate aminotransferase, obesity, Nordic Walking, Pilates.